The Principal's Collegial Leadership Model and Its Impact on Islamic Religious Education Teacher Motivation at Muhammadiyah Berau Vocational School - Syamsul Kamar TN; Khamam Khosiin; Benny Prasetya (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
Islamic Religious Education teachers in vocational schools require effective and supportive principal leadership to maintain work motivation, strengthen professional competence, and integrate Islamic values within the specific demands of vocational education. This study aims to analyze the collegial leadership model of the principal and its impact on the motivation and achievement of Islamic Religious Education teachers at SMK Muhammadiyah Berau. This research used a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving the principal, Islamic Religious Education teachers, other teachers, and students as supporting informants. The data were analyzed through data condensation, data display, conclusion drawing, and verification. The findings show that the principal’s leadership plays an important role in improving Islamic Religious Education teachers’ motivation through open communication, exemplary behavior, teacher development meetings, training, internships, clear direction, and the strengthening of a collegial work culture. The strategy to improve teacher achievement was carried out through the development of teachers’ interests and talents, participation in internal teacher competitions, Ministry of Religious Affairs activities, Muhammadiyah activities, and provincial-level competitions. The impact of leadership can be seen in increased work enthusiasm, sense of belonging, discipline, teacher participation, and wider opportunities for professional self-development. The leadership model found in this study is a collective collegial leadership model based on Islamic values, which emphasizes deliberation, communication, professional development, achievement development, and an Islamic work culture. This study confirms that the motivation and achievement of Islamic Religious Education teachers are shaped not only by individual competence but also by the quality of principal leadership and the school work climate.